(untitled) (Research, Society and Development, 2020)
Fractures of the Zygomaticomaxillary Complex Fracture (ZMC) are among the main injuries of maxillofacial trauma and knowing their demographic patterns is essential for prevention and treatment. Therefore, the aim of this study was to research the etiology, incidence and treatment choice of these fractures at the Oral and Maxillofacial Surgery Service of the Padre Bento Hospital Complex, Guarulhos, SP, Brazil. A retrospective epidemiological study of patients with ZMC fracture between 2017 and 2018 was carried out. In a population of 84 patients with ZMC fracture, 54 entered the study. Data related to sex, age, fracture etiology and treatment of choice were collected from the hospital’s handbooks. There was female predominance, between 20 and 40 years in 2017 and 51 and 70 years in 2018. The main etiologies were car accidents, falls from a height and physical aggression, with data variation between the period studied. In 2017, the main treatment performed among men was non-surgical (57.14%) and in 2018, surgical (68.42%). Nasal fracture was the most associated fracture in both genders. The fracture of ZMC is more prevalent in men, with car accidents, falls from a height and physical aggressions being the main etiologies of the studied region. The information presented elicited data to clarify the type of attendance performed by the service. This information can compare with data among services, in addition to contributing to fracture prevention policies.